Perbandingan Aktivitas Antibakteri Berbagai Produk Hand Sanitizer terhadap Escherichia coli dan Staphylococcus aureus In Vitro - Simaremare, Ade Pryta Romanauli (Universitas HKBP Nommensen, 2023)
Background: Hand hygiene is very important because human hands are often contaminated with microorganisms, so that it becomes an intermediary for the entry of disease-causing microorganisms into the body, especially Escherichia coli and Staphylococcus aureus. The use of hand sanitizer has shown an increase in society. Hand sanitizers are available with various types of packaging, dosage forms, variations in the composition of active ingredients and their carriers at quite competitive prices.Objective: To determine the antibacterial effect of various hand sanitizers available in the market and their comparison with antiseptic handwash soap.Methods: Antibacterial effectiveness test using the Kirby Bauer method by measuring the diameter of the clear zone produced on Muller Hinton media by diffusion discs tested with four hand sanitizer products available in the market compared with antiseptic hand soap as positive control and akuades as negative control.Results: Various hand sanitizer products containing 70% alcohol showed moderate to strong inhibition against E. coli and S.aureus. Analysis of differences in the activities of various hand sanitizer products using the KruskalWallis non-parametric method showed a difference with p= 0.003 against E. coli and p=0.002 against S.aureus. Alcohol denatures bacterial proteins so that it interferes with the metabolic processes of bacterial cells which causes bacterial cell death.Conclusion: Hand sanitizer is effectively used to inhibit the growth of E. coli and S.aureus bacteria.